Delphi study among international expert panel to develop waterpipe-specific health warning labels. Issue 2 (29th January 2019) - Asfar, Taghrid; Schmidt, Michael; Ebrahimi Kalan, Mohammad; Wu, Wensong; Ward, Kenneth D; Nakkash, Rima T; Thrasher, James; Eissenberg, Thomas; Ben Romdhane, Habiba; Maziak, Wasim
Abstract : Background: Waterpipe (WP) smoking is increasing globally. The rise of WP has been fuelled by widespread misperception of reduced-harm compared to cigarettes. Health warning labels (HWLs) are one strategy to communicate smoking-related risks and address reduced-harm misperceptions. Therefore, the development of WP-specific HWLs represents a priority for WP control. Methods: A panel of experts in WP science developed 28 WP-specific HWLs corresponding to five themes (health risks, addiction, harm to others, WP-specific harm, WP harm compared to cigarettes). Subsequently, a three-round Delphi study was conducted among international expert panel to reach consensus on a set of the most effective HWLs for each theme. Levels of agreement between participants were assessed using interquartile deviations, and the rank between the tied HWLs was based on the median. Results: Starting with 28 candidate HWLs stratified according to five WP-related themes, our international expert panel reached consensus on the 13 most important WP-specific HWLs. Labels with the highest agreement were related to oral and heart disease, WP's harmful effects on newborn children and the amount of smoke inhaled from WP compared to cigarettes. Conclusion: This study is the first to systematically develop and evaluate potential WP-specific HWLs based on the scientific evidence about WP's harmful effects, scientific understanding of HWL for cigarettes and the opinions of experts in WP science, tobacco control and health communication. The final selected HWLs can be adapted based on the context and policy landscape of the target country and can be further fine-tuned based on feedback from WP smokers and non-smokers.